Treatment of Diabetes, Asthma, Migraine, Arthritis, Digestion and Cholesterol with Green Tea Herbal Infusion of Happy Life India Tea Products: Health Benefits of Green Tea Infusion (Journal of Advances and Scholarly Researches in Allied Education, 2019)
These days Tea for health, Tea for asthma or tea for asthmatic patient, Tea for Diabetes, Tea for Diabetic patients, Tea for Migraine, Depression, Stress, Anxiety, Tea for Cholesterol is the terms which are mostly searched on internet. Actually most of the diseased patients have gone deeply fed up taking allopathic, and other medicines, with regular psychological depression and body weakness, and therefore so many researchers are at work of finding something which could cure their disease with a routine intakes such as lunch dinner breakfast or tea. After a long research a company “HAPPY LIFE INDIA” prepared a blended formula of some herbs commonly used in kitchen also. This formula was tested with green tea infusion and gave effective results on asthmatic, diabetic, arthritis, gout, migraine, heart and gastric patients.The different products of green tea infusion with tulsi, ginger, mulethi, adusa and clove, amla, marod fali, stevia, paneer phool, ashwagandha, samalpanja, shatavar, konch beej and many herbs were found fast resulting and most relaxing ingredients for asthmatic, diabetic, arthritis, gout, migraine, heart and gastric patients problems.Key Words Green Tea for Asthma treatment, Treatment of Diseases with Tea, Tea for Diabetes, Tea for Arthritis, Tea for Migraine, Tea for cholesterol, Tea for Digestion, Stevia, Tea for Green tea, Herbs, Ginger, Happy Life India